2022
DOI: 10.1002/elan.202200031
|View full text |Cite
|
Sign up to set email alerts
|

Multi Wavelengths Fusion Profiling for Quality Evaluation of Donglingcao Tablets Combined with Electrochemical Oscillation Fingerprints and Antioxidant Activity Analysis

Abstract: For a long time, Donglingcao tablets (DLCT) has been considered as a valuable traditional Chinese medicine (TCM) preparation. The five-wavelength fusion fingerprints (FWFFP) of 16 batches of DLCT, which avoided fluctuation of single wavelength evaluation, were established to analyze fingerprint similarity by ratio fingerprint quantitative method (RFQM). Furthermore, electrochemical oscillation fingerprints (ECOFP) of DLCT from different manufacturers were studied by Belousov Zhabotinskii (B-Z) oscillating syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…2F , the evaluation results for the same sample at five wavelengths differed, making the quality assessment using a single wavelength somewhat biased. FMAFFP synthesized the fingerprint data at each wavelength, resulting in more precise and comprehensive evaluation results [35] . The modest variation range of S L suggested that the chemical compositions of samples were distributed similarly.…”
Section: Resultsmentioning
confidence: 99%
“…2F , the evaluation results for the same sample at five wavelengths differed, making the quality assessment using a single wavelength somewhat biased. FMAFFP synthesized the fingerprint data at each wavelength, resulting in more precise and comprehensive evaluation results [35] . The modest variation range of S L suggested that the chemical compositions of samples were distributed similarly.…”
Section: Resultsmentioning
confidence: 99%
“…15 Three experiments were linearized using quantum fingerprinting and quantization is a digitization assignment process, which is a digitization of continuous signals, full-value informatization, and original chromatographic transformation of the original signal completeness. 16 In addition, using a B-Z electrochemical oscillation system, 17 electrochemistry is an analytical technique based on the phenomenon of chemical oscillations. When different substances are added to a system, the chemical substances contained in it will participate in an oscillatory reaction, causing the damped oscillations to eventually stop for a finite period of time, 18 and the shape of the curve and information on the specific parameters can reflect the differences in the samples, and thus can be used for identification or quality evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, using a B–Z electrochemical oscillation system, 17 electrochemistry is an analytical technique based on the phenomenon of chemical oscillations. When different substances are added to a system, the chemical substances contained in it will participate in an oscillatory reaction, causing the damped oscillations to eventually stop for a finite period of time, 18 and the shape of the curve and information on the specific parameters can reflect the differences in the samples, and thus can be used for identification or quality evaluation.…”
Section: Introductionmentioning
confidence: 99%